Single phase nanofluids in fluid mechanics and their hydrodynamic linear stability analysis. (April 2020) - Turkyilmazoglu, Mustafa
Highlights: An adjusting parameter to show the stability is introduced. Correlations for one phase fluid models are constructed. The critical Reynolds number of nanofluids is estimated from the pure one. The stabilizing/destabilizing effects of nanoparticles are easy to discover. Abstract: Background and objective: The hydrodynamic stability of nanofluids of one phase is investigated in this paper based on linear stability theory. The overall thrust here is that the linear stability features of nanofluids can be estimated from their corresponding working fluid, at least in special circumstances. Methods: The approach uses the adjusting parameter to make assertions about stability. This is possible by certain correlations between the resulting eigenvalues. Results: It is shown that as the nanoparticles are added, the mean flow of nanofluids is slightly modified and the resulting eigen space of nano disturbances is built on the corresponding pure flow eigen space of perturbations. Several fluid dynamics problems are revisited to verify the usefulness of the obtained correlations. Conclusion: The presented approach in this work serves us to understand the stabilizing/destabilizing effects of nanofluids as compared to the standard base fluids in terms of stability of viscous/inviscid and temporal/spatial senses. To illustrate, the critical Reynolds number in a traditional boundary layer flow is shown to be pushed to higher values with the dispersed nanoparticles in a working fluid, clearly implying the delay in transition from laminar to turbulent state.